2016
DOI: 10.1073/pnas.1605849113
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral tolerance can be modified by altering KLF2-regulated Treg migration

Abstract: Tregs are essential for maintaining peripheral tolerance, and thus targeting these cells may aid in the treatment of autoimmunity and cancer by enhancing or reducing suppressive functions, respectively. Before these cells can be harnessed for therapeutic purposes, it is necessary to understand how they maintain tolerance under physiologically relevant conditions. We now report that transcription factor Kruppel-like factor 2 (KLF2) controls naive Treg migration patterns via regulation of homeostatic and inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 57 publications
(51 reference statements)
1
24
0
Order By: Relevance
“…Of note, we also identified additional upstream regulators, either previously reported or of interest for future studies: MYB, SATB1, NFATC2, KLF2, ZBTB16 , and DDIT3 were all found to be significant upstream regulators across the Treg subpopulations. Treg-specific roles for MYB 33 , SATB1 34 , NFATC2 35 , and KLF2 36 have already been demonstrated in maintaining Treg functional properties, supporting the validity of our upstream regulator analysis. Given that these factors have a capacity to interact with β-catenin, for example, β-catenin can form a complex with SATB1 and modulate Th2 cell differentiation 62 , it is likely that these factors can interact to establish a complex regulatory system in Treg homeostasis.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Of note, we also identified additional upstream regulators, either previously reported or of interest for future studies: MYB, SATB1, NFATC2, KLF2, ZBTB16 , and DDIT3 were all found to be significant upstream regulators across the Treg subpopulations. Treg-specific roles for MYB 33 , SATB1 34 , NFATC2 35 , and KLF2 36 have already been demonstrated in maintaining Treg functional properties, supporting the validity of our upstream regulator analysis. Given that these factors have a capacity to interact with β-catenin, for example, β-catenin can form a complex with SATB1 and modulate Th2 cell differentiation 62 , it is likely that these factors can interact to establish a complex regulatory system in Treg homeostasis.…”
Section: Discussionsupporting
confidence: 81%
“…Together, these results suggest that β-catenin plays a critical role in driving the production of both IFNγ and IL-10 in Tregs, especially for IFNγ. We also identified several upstream regulators that have been demonstrated to have critical roles in maintaining Treg function, including MYB 33 , SATB1 34 , NFATC2 35 , and KLF2 36 , suggesting that our upstream regulator analysis provides a reliable readout.…”
Section: Resultsmentioning
confidence: 80%
“…Many of these genes, namely, NT5E, FOXO1, S1PR1, LGMN, KLF, DUSP5, and DUSP6, have been described to have a potential role in T reg development and function ( Fig. 3D) (22)(23)(24)(25)(26)(27)(28).…”
Section: Foxp3 A384t Partially Establishes the Foxp3-driven Genetic Pmentioning
confidence: 99%
“…Alternatively, changes in the migration patterns of Tregs could explain this preferential enrichment in lymphoid tissues, because of the modulation of chemokines and adhesion molecules by statins (20, 37, 41). Remarkably, this Treg accumulation in lymphoid tissue could be critical for the establishment and regulation of an efficient antigen-specific immune response.…”
Section: Discussionmentioning
confidence: 99%